Obligatory Controlled Subjects In Bùlì - Sulemana, Abdul-Razak (My University, 2022)
The paper argues that despite the lack of morphological marking to distinguish between finiteness and nonfiniteness, such a distinction does exist in Bùlì. It also argues that unlike the nonfiniteness of the English type languages where nonfinite clauses take a null subject (PRO), the nonfinite clauses of Bùlì obligatorily take overt pronominals. The fact that the controlled element is overt in the language, I argue, shows that phonetic nullness is not an inherent property of the controlled element.
Keywords: Bùlì; nonfinite clauses; morphological marking; language; overt pronomials